Empirical Magnetic Structure Solution of Frustrated Spin Systems - Paddison, J; Goodwin, A (2012)
Frustrated magnetism plays a central role in the phenomenology of exotic quantum states. However, since the magnetic structures of frustrated systems are often aperiodic, there has been the problem that they cannot be determined by using traditional crystallographic techniques. Here we show that the magnetic component of powder neutron scattering data is actually sufficiently information-rich to drive magnetic structure solution for frustrated systems, including spin ices, spin liquids, and molecular magnets. Our methodology employs ab initio reverse Monte Carlo refinement, making informed use of an additional constraint that minimizes variance in local spin environments. The atomistic spin configurations obtained in this way not only reflect a magnetic structure "solution" but also reproduce the full three-dimensional magnetic scattering pattern. © 2012 American Physical Society.